Zmiany w myśleniu o rozwoju ścieżki kariery zawodowej w świecie permanentnej zmiany - Myszka, Lucyna (Wydawnictwo Naukowe UAM, 2014)
The time of stable careers in one organization has gone. In a globalized world, the traditional way of career development is very rare. Today we can observe a negotiation between the employer and the employee about his/her future career. This situation demands an ability to quickly respond to the job market’s needs and to be proactive about one’s career. On the other hand, management has to be open to employees’ expectations. This provokes a question about reference points in a world of permanent change in relation to making one’s future.
Changes in the Way of Thinking About Career Development in the World of Permanent Change
Keywords: career paths; youths; job market; social change